45. RATE AND SOME FACTORS RELATED TO TRICHOMONAS TENAX INFECTION IN PERIODONTAL DISEASE PATIENTS COME FOR EXAMINATION AND TREATMENT AT THE CENTRAL HIGHLANDS GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the prevalence of Trichomonas tenax infection and describe some factors related to infection in patients with periodontitis who visited and were treated at the Central Highlands General Hospital in 2024.Methods: Cross-sectional study design on 425 patients diagnosed with periodontitis and tested for T. tenax by microscopy, conducted from January to December 2024. Demographic and behavioral data were collected using an interview questionnaire.Results: The prevalence of T. tenax infection was 27.53%. The age group over 60 had the highest prevalence (41.67%), followed by the age group 15-60 (27.50%) and under 15 (8.89%). The prevalence of infection was higher in men than in women (30% vs. 24.62%), but not statistically significant. Smokers had a significantly higher risk of infection (37.38% vs. 24.21%; p < 0.05). The infection rate increased with the level of poor oral hygiene: from 16.67% (level 0) to 61.22% (level 3). The group with low education level (illiteracy and primary school) had a higher infection rate than the group with high education. Patients with comorbidities such as diabetes (58.82%) and hypertension (36.36%) had a higher risk of infection than the group without underlying diseases.Conclusion: The rate of T. tenax infection in patients with periodontitis was significant. Factors closely related to the risk of infection included old age, smoking, poor oral hygiene, low education level and comorbidities such as diabetes. It is necessary to strengthen oral health education and parasite screening in high-risk groups.
Keywords: Trichomonas tenax; periodontitis; oral hygiene; risk factors.